Coupling investigation on tensile and acoustic absorption properties of lightweight porous LGF/PP composite. Issue 4 (1st April 2018) - Mo, Fuhao; Zhang, Haiyang; Yang, Xujing; Duan, Shuyong; Xiao, Zhi
Abstract : Long glass fiber‐reinforced polypropylene (LGF/PP) foaming composite has been increasingly used in automotive components regarding its good mechanical and acoustic properties. However, the balance of its mechanical property and acoustic property is far from being understood. The objective of this study is to investigate the influences of molding thickness or foaming degree on both mechanical and acoustic properties of LGF/PP foaming composite by experimental tests. First, LGF/PP foaming composite felts with consistent surface density were fabricated, then specimens with a series of molding thicknesses were prepared by compression molding. Tensile and acoustic tests were conducted and a scanning electron microscopy was also used for analyzing microscopic characteristics. The results indicate that tensile strength and tensile modulus of the present LGF/PP composite decrease in exponential formats, whereas sound absorption coefficients of them increase in logarithmic formats, when molding thickness vary from 1.5 to 8 mm. The above curves intersect around 3 mm. Thus, both mechanical and acoustic properties should be balanced regarding structural size when designing a multi‐purpose vehicle component using the present composite. POLYM. COMPOS., 40:1315–1321, 2019. © 2018 Society of Plastics Engineers